THE INFLUENCE OF TEACHERS TEACHING STYLES ON MOTIVATION AND LEARNING OUTCOMES OF BIOLOGY ON THE CONCEPT OF THE HUMAN CIRCULATION SYSTEM OF CLASS VIII STUDENTS OF SMP HANG TUAH LANTAMAL IX AMBON - Bulohroy, Aknes Gerce; Salmanu, Sriyanti Imelda Aksamina; Rehena, Johanis Fritzgal (RUMPHIUS, 2022)
Education and teaching focusing on the interaction between educators with educated or teachers with students. The interaction of teachers and teaching in improving stundent learning outcomes especially on biological materials, desperately needs attention, motivation, and interest. It almost entirely uses a good teaching style. This study was conducted for 1 month starting from 05th of November until 05th of Desember 2021. The purpose of this study is to influence of teacher’s teaching style (Variable X) and motivation of student learning outcomes in Biology at SMP Hang Tuah Lantamal IX Ambon by taked sample of 35 respondents, are the students of class VIII. The results showed that there is a significant influence or perfect correlation between teacher teaching styles on the motivation of learning results ofhuman’s blood circulation system in grade VIII of SMP Hang Tuah Lantamal IX Ambon. It is provenby the product moment correlation value of pearson rarithematic = 1.00 when compared with rtable = 0, 334 and according to table interpretstion of pearson correlation coefficient. Thus the hypothesis H1 which states there is a significant influence between teacher teaching style on student learning outcomes motivation.